Direct and indirect effects of the Right to Education Act on the enrolment of disadvantaged groups in India - Athira Vinod (The University of Nottingham, Centre for Research in Economic Development and International Trade (CREDIT), 2024)
Using longitudinal school data from India, this paper examines enrolment trends of socially disadvantaged children post the Right to Education (RTE) Act, which mandated the reservation of 25% of private school places for such children. Post-RTE, a significant increase is observed in disadvantaged children attending private schools. Difference-in-differences analysis reveals greater increases in schools previously below the 25% quota, especially those participating in the reservation policy. The results are however driven by a 'substitution' of places, where private schools are replacing free places under the policy with fee-paying disadvantaged children.
Keywords: I21; I22; I24; I28; 330; Private schools; Disadvantaged groups; Right to Education Act; Reservation policy